Single-phase cascaded t and π-type grid-connected PV inverters with capacitor voltage balancing / Aamir Amir - Aamir , Amir (2019)
This thesis presents the development of single-phase T and π-type Cascaded H-Bridge inverters for a grid-connected photovoltaic (PV) system. The T-type Cascaded H-Bridge (TCHB) single-phase inverter utilizes two T-type Bidirectional Switches (BSs) and is capable of generating an output-voltage of nine levels (2Vdc, 3Vdc/2, Vdc, Vdc/2, 0, −Vdc/2, −Vdc, −3Vdc/2, −2Vdc) from two separate dc supply voltages. The π-type Cascaded H-Bridge (PiCHB) single-phase inverter employs two π-type BSs and can produce an output-voltage of thirteen levels (2Vdc, 5Vdc/3, 4Vdc/3, Vdc, 2Vdc/3, Vdc/3, 0, −Vdc/3, −2Vdc/3, −Vdc, −4Vdc/3, −5Vdc/3, −2Vdc) from two separate dc supply voltages. In addition, to validate the improved performance of the suggested structures, the TCHB and PiCHB topologies are compared against various other symmetric cascaded topologies, considering the parameters of number of switches